Evaluation Of The Implementation Of Deep Learning Approach Based On Context, Input, Process, Product (CIPP) In Elementary Schools Of Tomohon City - Jamalri Pajow; Joulanda A.M. Rawis; Non Norma Monigir (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to evaluate the implementation of the deep learning approach based on the CIPP (Context, Input, Process, Product) model in elementary schools in Tomohon City. It employs a qualitative approach with an evaluative research type. The research subjects consisted of principals, teachers, and students at SD GMIM IV and SD GMIM 7 Tomohon. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that: (1) the context aspect has a strong foundation, supported by student needs and the Merdeka Curriculum policy; (2) the input aspect shows adequate resource readiness, yet teacher competency still needs improvement; (3) the process aspect has moved toward active learning, although not consistently across all classrooms; and (4) the product aspect shows increased student motivation, participation, and learning outcomes. In conclusion, the implementation of CIPP-based deep learning in Tomohon City elementary schools has been running well, but still requires strengthening in the process aspect and teacher competency development for more optimal results. Keywords deep learning, CIPP evaluation, elementary school, Merdeka curriculum